Cover Picture: Addressing Environmental Challenges of Porphyrin Mixtures Obtained from Statistical Syntheses (Chemistry ‐ Methods 3/2021). Issue 3 (23rd February 2021) - Hölzel, Helen; Muth, Maximilian; Lungerich, Dominik; Jux, Norbert
Abstract : The Front Cover shows a laboratory bench, with instruments, equipment, and a chalkboard. Is there a way to implement the philosophy of "reduce, reuse and recycle" in academic research? The recycle sign underlines the rising awareness for this topic, which is steadily gaining in importance. Especially in porphyrin sciences, using semi‐automated flash chromatography can decrease significantly the cost of consumables, such as chlorinated solvents and silica gel. With a re‐usable glass column for preparative separation, even the purification of statistical reaction mixtures can be managed, while reducing the waste and thus the environmental factor significantly. More information can be found in the Full Paper by Dominik Lungerich, Norbert Jux and co‐workers .